Replacement of Traditional Nursing Clinical With a Virtual Simulated Clinical Experience During the COVID-19 Pandemic (International Journal of Studies in Nursing, 2022)
Background: In response to the COVID-19 pandemic, Indiana University (IU) South Bend nursing faculty created a virtual clinical day that included synchronous and asynchronous experiences to replace 50% of traditional clinical hours in a 1:1 exchange to realistically imitate an in-person clinical day. Purpose: The purpose of this study was to evaluate existing outcome data to support the replacement of a traditional clinical experience with a virtual clinical experience as a valid pedagogical strategy to meet clinical student learning outcomes. Methods: Descriptive statistics were used to measure mean values of evaluation data for students who participated in the virtual simulated clinical experience (VSCE). Additionally, aggregate final course grades were compared between the group of students who participated in the VSCE and those who did not. Results: When compared with a traditional clinical day, all respondents believed that the VSCE was equal to or better than the traditional clinical setting for promoting critical thinking and meeting course outcomes. Evaluation of final course grades in the corequisite didactic course demonstrated equal or better performance than students in the traditional clinical setting only. Conclusion: Even though this experiment resulted in a successful outcome, it is essential to continue with rigorous research to demonstrate the effectiveness of a virtual clinical experience as a substitute for face-to-face clinical or simulation hours.